If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -1(-5) = -6(x + -1) Multiply -1 * -5 y + 5 = -6(x + -1) Reorder the terms: 5 + y = -6(x + -1) Reorder the terms: 5 + y = -6(-1 + x) 5 + y = (-1 * -6 + x * -6) 5 + y = (6 + -6x) Solving 5 + y = 6 + -6x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + y = 6 + -5 + -6x Combine like terms: 5 + -5 = 0 0 + y = 6 + -5 + -6x y = 6 + -5 + -6x Combine like terms: 6 + -5 = 1 y = 1 + -6x Simplifying y = 1 + -6x
| 2x-71.50=4308.50 | | x+(x+5)+(2x+11)=180 | | 3/4y-6=0 | | x-20+x= | | 695=13(k+5)+32 | | logx=0.45 | | 7b=85 | | 10(g-836)=740 | | 5x-5(-6-2x)=0 | | 5-7x=2x+8 | | 2-2y-3y=0 | | 9x-(3x+3)=4x-49 | | -2=6-x | | 29=2+3g | | 8(4w+9)=-8 | | 4x^2-11x+15=0 | | 9r+8s-5(8r-5s)= | | 3x^2+12x-24=-26 | | 1/3x^2-1/12x-1/6=0 | | 803=792-b | | -6(q-81)=-30 | | 4.3(4+2x)-4.2=13 | | 2(8x+4)=22x | | -10(s+5)=-101 | | Ln(5/x)=-2 | | k^2-4k-2=0 | | 9x+8y-5(8x-5y)= | | 3(s+11)+22=76 | | 4(3p+1)=64 | | Tan(60)=x/9 | | Lm(5/x)=-2 | | 4(z-66)-97=-33 |